1990
DOI: 10.1111/j.1469-8137.1990.tb00450.x
|View full text |Cite
|
Sign up to set email alerts
|

The biology of mycorrhiza in the Ericaceae

Abstract: , 1985 ;Denny & Wilkins, 1987). In the case without its mycorrhizal endophyte, over a range of of metals such as iron, which are essential in small concentrations of either of two calcium salts, the quantities for normal plant function, but which mycorrhizal (M) plants captured significantly more become potentially toxic as their availability iron. Increases in iron uptake took place in all Ca mcreases, it is the regulation of supply across a wide treatments, and were of such magnitude as to range of concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 27 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…In contrast to VAM, many studies have shown that ECM and EM fungi can utilize organic N sources through the production of extracellular acid proteinases (Leake and Read, 1990;Zhu et al, 1990;Maijala et al, 1991; Fig. 1).…”
Section: Nitrogenmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to VAM, many studies have shown that ECM and EM fungi can utilize organic N sources through the production of extracellular acid proteinases (Leake and Read, 1990;Zhu et al, 1990;Maijala et al, 1991; Fig. 1).…”
Section: Nitrogenmentioning
confidence: 95%
“…Conclusions upon the importance of siderophore production of ECM fungi for the Fe nutrition of the host plant and its adaptation to calcareous soils (Lapeyrie, 1990) are merely based on observations rather than measurements. In EM, however, experimental evidence has been presented for higher affinity of EM roots for Fe and h i g h e r u p t a k e rates at low e x t e r n a l concentrations (Shaw et al, 1990).…”
Section: P R O D U C T I O N Of S I D E R O P H O R E S Is W I D E S mentioning
confidence: 98%
“…These structures provide plants with nitrogen and phosphorus and protect plants from disease (18) and heavy metal contamination (34,52). Different fungal species, and even isolates of the same species, can vary in their tolerance of harsh conditions (33,50) and in the ability to help plants grow in extreme environments, such as acidic mine tailings (51) and coal spoils (24,28).…”
mentioning
confidence: 99%
“…Shoot to root ratios of Fe content (Ixg/g) of mycorrhizal plants were always lower than those of nonmycorrhizal plants, indicating that proportionally less Fe was transported to the shoots of mycorrhizal plants (Table 1). Shaw et al (1990) reported that growth of H. ericae was not inhibited in solution cultures containing an external range of 0-144 I~g/ml Fe. The present investigation showed a stimulation of fungal growth at 150 ~g/ml Fe compared to the control but a reduction in yield at higher Fe concentrations.…”
Section: Resultsmentioning
confidence: 98%
“…The role of mycorrhizas in environments containing elevated and potentially toxic levels of heavy metals has received limited attention, but there is evidence that the success of ericaceous plants in some extreme terrestrial environments may be partly attributable to their mycorrhizal partners (Bradley et al~ 1981;Burt et al 1986;Hashem 1990;Leake et al 1990;Shaw et al 1990). Shaw et al (1990) …”
Section: Introductionmentioning
confidence: 98%